Hepato-protective effect of resveratrol against acetaminophen-induced liver injury is associated with inhibition of CYP-mediated bioactivation and regulation of SIRT1–p53 signaling pathways. Issue 2 (16th July 2015) - Wang, Ying; Jiang, Yiming; Fan, Xiaomei; Tan, Huasen; Zeng, Hang; Wang, Yongtao; Chen, Pan; Huang, Min; Bi, Huichang
Graphical abstract